MicroRNA-302a-3p induces ferroptosis of non-small cell lung cancer cells via targeting ferroportin - Wei, Dong; Ke, Yao-Qi; Duan, Peng; Zhou, Lei; Wang, Chang-Ying; Cao, Ping (Free radical research, 2021)
Ferroptosis is a newly described regulated form of cell death that contributes to the progression of non-small cell lung cancers (NSCLCs). MicroRNA-302a-3p (miR-302a-3p) plays critical roles in the tumorigenicity of different cancers; however, its function and underlying mechanism in ferroptosis and NSCLCs remain unclear. Human NSCLCs cells were incubated with miR-302a-3pmimic or inhibitor in the presence or absence of erastin or RSL3. Cell viability, colony numbers, lactate dehydrogenase (LDH) releases, lipid peroxidation and intracellular iron level were measured. Besides, the synergistic effects of cisplatin and paclitaxel with miR-302a-3p were determined. miR-302a-3p level was reduced in human NSCLCs cells and tissues. ThemiR-302a-3p mimic induced lipid peroxidation, iron overload and ferroptosis, thereby inhibiting cell growth and colony formation of NSCLCs cells. Conversely, the miR-302a-3p inhibitor block ederastin- or RSL3-related ferroptosis and tumor suppression. Additionally, we found that miR-302a-3p directly bound to the 3′-untranslational region of ferroportin to decrease its protein expression, and that ferroportin overexpression significantly prevented miR-302a-3p mimic-induced ferroptosis and tumor inhibition. Moreover, the miR-302a-3p mimic sensitized NSCLCs cells to cisplatin and paclitaxel chemotherapy. miR-302a-3p functions as a tumor inhibitor, at least partly, via targeting ferroportin to induce ferroptosis of NSCLCs.